Content analysis of food advertisements on popular indian television channels among children and youth: a cross-sectional study - Shalini Bassi; Deepika Bahl; Heeya Maity; Sakshi Dudeja; Vani Sethi; Monika Arora (Journal of Global Health Reports)
# Background